2010
DOI: 10.1021/ac902596b
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-Assisted Cell Seeding in a Microwell Cell Culture System

Abstract: We present a simple method to actively pattern individual cells and groups of cells in a polymer-based microdevice using vacuum-assisted cell seeding. Soft lithography is used to mold polymer microwells with various geometries on top of commercially available porous membranes. Cell suspensions are placed in a vacuum filtration setup to pull culture medium through the microdevice, trapping the cells in the microwells. The process is evaluated by determining the number of cells per microwell for a given cell see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Toward Cell Clusters Consistent with previous observations, [5][6][7]12,24,37 PANC-1 cells at and near confluence formed 3D multicellular clusters when cultured in SFM (Supplementary Movie S1). In an attempt to explain the sixfold increase in migration rate and subsequent clustering of pancreatic cells upon the removal of serum, Hardikar et al suggested that serum could contain ''inhibitory factors'' that restrict cell migration.…”
Section: Panc-1 Cells Do Not Exhibit Preferential Migrationsupporting
confidence: 90%
See 1 more Smart Citation
“…Toward Cell Clusters Consistent with previous observations, [5][6][7]12,24,37 PANC-1 cells at and near confluence formed 3D multicellular clusters when cultured in SFM (Supplementary Movie S1). In an attempt to explain the sixfold increase in migration rate and subsequent clustering of pancreatic cells upon the removal of serum, Hardikar et al suggested that serum could contain ''inhibitory factors'' that restrict cell migration.…”
Section: Panc-1 Cells Do Not Exhibit Preferential Migrationsupporting
confidence: 90%
“…18,21,33 To fill the unmet need for insulin producing cells and improve long-term efficacy of treatment, researchers have explored alternative sources of insulin-secreting cells that include the self-replication of beta cells, differentiation of progenitor or stem cells, and transdifferentiation of related cell types toward a pancreatic endocrine phenotype. 2,5,12,27,30 The upregulation of islet cell hormone genes (e.g., insulin, glucagon, c-peptide, and somatostatin) and their secretion are associated with clustering and the transition from a two-dimensional monolayer to three-dimensional islet-like structures in vitro. [5][6][7]24,37 Further supporting the importance of the 3D structure is the observation that the secretory responsiveness of cells in 3D clusters was lost upon dispersal of the cells and established again after 3D isletlike structures were reformed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in certain encapsulation systems, the gel material provides an additional barrier that affects the diffusion of important factors (e.g., oxygen, glucose, insulin) into and out of the aggregate (Hulst et al 1989;Lovett et al 2009;Li et al 1996;Khattak et al 2007;Beck et al 2007). More recently, microfabrication techniques have been applied to develop a number of systems that could be used to create cell aggregates in a more controlled and efficient manner, via passive (e.g., cell sedimentation) and/or active (e.g., vacuum, surface functionalization, dielectrophoretic forces) means (Karp et al 2007;Moeller et al 2008;Fukuda et al 2006;Mendelsohn et al 2010;Albrecht et al 2006;Ferrell et al 2010;Bernard et al 2012). Among these, microwell-based devices have been consistently used to create clusters with multiple cell types.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying porosity was attained by interfacing the microwells with a bed of electrospun polycaprolactone (PCL)-gelatin micro/nano fibers, which confers a number of advantages over previously developed microwell-based systems; including fiber-based biomimicry and improved mass transfer Ferrell et al 2010;Li and Xia 2004;Lannutti et al 2007;Schindler et al 2005;Toh et al 2006;Lim and Mao 2009;Nisbet et al 2009;Nur-E-Kamal et al 2006;Zhao et al 2010). Polyblend fibers have been increasingly used in cell culture applications as these systems have the potential to resemble more closely the complexity of the extracellular matrix (Gunn and Zhang 2010;Woodruff and Hutmacher 2010;Heydarkhan-Hagvall et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation